2017
DOI: 10.1007/s11748-017-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Total aortic arch replacement using frozen elephant trunk technique with J Graft Open Stent Graft for distal aortic arch aneurysm

Abstract: Our short-term surgical results were acceptable. This new device is useful for distal aortic arch aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…When we compared studies performed only in patients with acute type A aortic dissection (n ¼ 12, 1300 patients) 21,23,25,[27][28][29][30]35,37,41,46,47 with studies performed only in patients with nonacute type A dissection and aneurysm (n ¼ 14, 741 patients), 14,15,17,19,22,[24][25][26]34,40,[42][43][44][45] we found the following results: The pooled mortality rate was 9.2% (95% CI, 6.9-12.4) in the patients with acute type A and 7.6% (95% CI, 4.9-11.4) in the patients with nonacute dissection and aneurysm (P ¼ .46). The pooled rate of stroke in these 2 groups was 9.3% (95% CI, 4.5-18.5) and 6.6% (95% CI, 3.1-13.5) (P ¼ .51), and the pooled rate of SCI was 2.4% (95% CI, 1.3-4.2) and 5.2% (95% CI, 3.1-8.5) (P ¼ .05), respectively ( Figure E2).…”
Section: Acute Type a Versus Nonacute Type A And Aneurysmmentioning
confidence: 99%
“…When we compared studies performed only in patients with acute type A aortic dissection (n ¼ 12, 1300 patients) 21,23,25,[27][28][29][30]35,37,41,46,47 with studies performed only in patients with nonacute type A dissection and aneurysm (n ¼ 14, 741 patients), 14,15,17,19,22,[24][25][26]34,40,[42][43][44][45] we found the following results: The pooled mortality rate was 9.2% (95% CI, 6.9-12.4) in the patients with acute type A and 7.6% (95% CI, 4.9-11.4) in the patients with nonacute dissection and aneurysm (P ¼ .46). The pooled rate of stroke in these 2 groups was 9.3% (95% CI, 4.5-18.5) and 6.6% (95% CI, 3.1-13.5) (P ¼ .51), and the pooled rate of SCI was 2.4% (95% CI, 1.3-4.2) and 5.2% (95% CI, 3.1-8.5) (P ¼ .05), respectively ( Figure E2).…”
Section: Acute Type a Versus Nonacute Type A And Aneurysmmentioning
confidence: 99%
“…Koizumi et al reported a similar operation technique done on 30 patients with distal aortic arch aneurysm, with acceptable results (30-day mortality, 0%; stroke, 10%; and paraplegia, 3%). 6 Yamamoto et al reported zone-0 anastomosis TAR using FET for patients with AADA, where they also utilized extra-anatomical reconstruction of the left subclavian artery. 21 The advantage of such proximalized TAR using FET with extra-anatomical reconstruction of the left subclavian artery is not only the merit of avoiding deep distal anastomosis but also avoiding in-situ reconstruction of the left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Since the commercialization of a novel frozen elephant trunk (FET) device in Japan, 6 7 we have been performing “proximalized” TAR, in which the standard procedure for distal anastomosis is done between the left subclavian artery and the left common carotid artery (zone 2), between the left common carotid artery and the brachiocephalic trunk (zone 1), or at the ascending aorta (zone 0). This proximalized TAR was also performed by trainees as surgical education.…”
Section: Introductionmentioning
confidence: 99%
“…Of 64 studies reporting outcomes of patients included in this report 13–76 . The proportions of studies from Asia, Europe, and North America were 54.7%, 31.3%, and 10.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%